2010
DOI: 10.3109/00365591003727569
|View full text |Cite
|
Sign up to set email alerts
|

Effect of output voltage distribution on stone comminution efficiency during shockwave lithotripsy in renal or ureteropelvic junction stones: A preliminary study

Abstract: In this preliminary study, manipulation of the lithotripter output voltage distribution did not affect stone comminution efficiency for renal or UPJ stones. This finding should be confirmed by larger studies including more patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 21 publications
(32 reference statements)
0
2
0
Order By: Relevance
“…Although their study was based on one-time voltage escalation but not gradual voltage escalation, it suggested that voltage escalation may be inferior to conventional fixed voltage. A previous study of Korean patients reported no significant difference in SFRs according to output voltage [13]. Although the reason for negative results in the two aforementioned studies [12,13] remains unclear, different study protocols, including voltage setting, shockwave numbers at low voltage, and frequency, may have contribute to conflicting results among the studies [7][8][9][10][11][12][13].…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Although their study was based on one-time voltage escalation but not gradual voltage escalation, it suggested that voltage escalation may be inferior to conventional fixed voltage. A previous study of Korean patients reported no significant difference in SFRs according to output voltage [13]. Although the reason for negative results in the two aforementioned studies [12,13] remains unclear, different study protocols, including voltage setting, shockwave numbers at low voltage, and frequency, may have contribute to conflicting results among the studies [7][8][9][10][11][12][13].…”
Section: Discussionmentioning
confidence: 96%
“…In vitro [7,8], animal [9], and two clinical trials [10,11] have shown better success rates using escalating voltage, compared to fixed voltage. In contrast, other randomized clinical trials showed no difference in treatment outcomes between fixed and escalating voltage [12,13]. The majority of subjects enrolled in the abovementioned studies were patients with renal calculi.…”
mentioning
confidence: 84%